BuMPing Into Neurogenesis: How the Canonical BMP Pathway Regulates Neural Stem Cell Divisions Throughout Space and Time - Le Dréau, Gwenvael (Frontiers in Neuroscience, 2022)
Bone morphogenetic proteins (BMPs) are secreted factors that contribute to many aspects of the formation of the vertebrate cen¬tral nervous system (CNS), from the initial shaping of the neural primordium to the maturation of the brain and spinal cord. In particular, the canonical (SMAD1/5/8-dependent) BMP pathway appears to play a key role during neurogenesis, its activity dictating neural stem cell fate decisions and thereby regulating the growth and homeostasis of the CNS. In this mini-review, I summarize accumulating evidence demonstrating how the canonical BMP activity promotes the amplification and/or maintenance of neural stem cells at different times and in diverse regions of the vertebrate CNS, and highlight findings suggesting that this function is evolutionarily conserved.